Strategic management and organisational dynamics : the challenge of complexity - Stacey, Ralph D. (Harlow, England ; New York : Prentice Hall/Financial Times, 2003)
In this fourth edition, the author continues to question the view that organizations operate and succeed in relatively stable environments. He argues that they must create new perspectives and learn from the chaos within which they operate.
Includes bibliographical references (p. [468]-478) and index.
oif 13/03/15
Loan
Keywords: Organizational behavior; Strategic planning; Strategic management; Organizational change